MATERNAL DETERMINANTS AND ACCESS TO HEALTH SERVICES IN RURAL AREAS OF WEST JAVA IN RELATION TO THE INCIDENCE OF STUNTING IN 2024 - Listiyaningsih, Erlin; Gayatri, Padma Vidya; Hanna, Henny (International Archives of Medical Sciences and Public Health, 2026)
Stunting remains a major public health problem in Indonesia despite national strategies implemented from 2018 to 2024 that reduced prevalence by nearly 9% through integrated nutrition-specific and nutrition-sensitive approaches. However, challenges persist in rural West Java, where prevalence increased slightly during 2021–2022, alongside disparities in education, nutrition behavior, and healthcare access. This study analyzes maternal determinants and access to health services related to stunting among 184 mothers of toddlers in rural Bogor using a cross-sectional design. Data were collected using validated questionnaires assessing nutrition knowledge, socioeconomic characteristics, and healthcare access. Results show a stunting prevalence of 45.6%, with maternal education (p=0.021), knowledge (p=0.023), feeding practices (p=0.022), and service access (p=0.029) significantly associated. These findings highlight maternal factors and service accessibility as key determinants requiring strengthened nutrition education and improved health service reach through community cadres to achieve national targets collectively.